Pemberdayaan Life Skill Peserta Didik Di SMK Muhammadiyah 6 Karanganyar - Mulyadi, Mulyadi; , Prof. Dr. Sutama, M.Pd (2015)
Description research general purpose to about empowerment of life skill educative participant in Vocational School Muhammadiyah 6 Karanganyar, while purpose of special of research, that is description about 1) Planning of life skill educative participant in Vocational School Muhammadiyah 6 Karanganyar; 2) Process life skill educative participant in Vocational School Muhammadiyah 6 Karanganyar. Research type is qualitative. Research approach applies phenomenology. Subjects were principals, chief program expertise, teachers, and the chairman of the workshop. Data collecting method applies in-depth interview, observation and documentation. Data analytical technique applies trianggulation. Result of research that is : 1) Planning of students life skills in Vocational School Muhammadiyah 6 Karanganyar is a school program to improve the life skills of learners who are prepared based on the results of deliberation principals, teachers in each field of expertise, and the teachers at Vocational School Muhammadiyah 6 Karanganyar. Forms of life skills planning of learners who do Vocational School Muhammadiyah 6 Karanganyar namely: Education Development Plan Oriented Life Skill (Life Skills Education), School Partnership Program with the company/industry, and Development of Unit Production Plan. 2) The process of life skills students in Vocational School Muhammadiyah 6 Karanganyar is the implementation of Life Skills Education plan, School Partnership Program plan with company/industry, and the development of Unit Production plan.